A Portraying English Language Learning Process: Speaking Activities of Young Learners at Boarding School - Khofiyatunnisa, Alya (Native: Journal of English Teaching and Learning, 2023)
This study aims to determine how the activities at boarding school train young learners in speaking English activities. This research approach is qualitative research. Observation interviews and questionnaires were used as data collection instruments. The subjects of this study were 20 male students from eighth grade and the English teacher at the Islamic boarding school Al-Basyariyah III. The results showed that the activities could trigger the success of students using English every day and student responses to one of the activities at boarding school had a positive impact on learning English and have an impact on improving English vocabulary and interest in learning English. It can be concluded that the various activities at boarding schools to improve students' speaking English can be a good recommendation and alternative. Keywords: Speaking Activities, ELL, Young Learners